HUBUNGAN PELAYANAN KEFARMASIAN TERHADAP KEPUASAN PASIEN PENGGUNA OBAT ANTI TUBERKULOSIS (OAT) DI UPT PUSKESMAS TITIPAPAN TAHUN 2021 - Manurung, Kesaktian; Sinaga, Taruli Rohana; Thaib, Cut Masyithah; Monica, Yohana (Jurnal Farmanesia, 2021)
. Patient satisfaction is the match between expectations and the reality felt by the patient. Pharmaceutical service is a direct and responsible service to patients, related to pharmaceutical preparations with the aim of achieving definite results to improve the quality of life of patients. The purpose of this study was to determine the level of patient satisfaction at UPT Puskesmas Titipapan and to determine the relationship between pharmaceutical services and patient satisfaction at UPT Puskesmas Titipapan. The population in this study were OAT users who were treated at UPT Puskesmas Titipapan Medan during this study. With an average number of 31 patients per month. The number of samples in this study was determined using theformula in slovin order to obtain a sample of as many as respondents who visited the UPT Puskesmas Titipapan. This research is a descriptive research with quantitative methods. The type of approach used is a cross sectional design, namely a research design that collects data at one time to the sample. The results of this study were the level of patient satisfaction at the UPT Puskesmas Titipapan Medan, 71.0% of patients felt very satisfied. Of the 25 patients (80.6%) who received good service, 9 patients (29.0%) were satisfied. Based on the statistical analysis of these values indicate that the level of quality pharmaceutical services provided by the UPT Puskesmas TitipapanPengg Patients AgainstunaAnti- Tuberculosis Drugs (AOT) is less significant.